Innovative volleyball training tool: AcuSpike drill with android sound reactions - Suhairi, Muhammad; Arifin, Zainal; Syaparudin (UIR Press, 2024)
Background Problems: The development of technology and sports science plays a crucial role in the world of sports. Research Objectives: The objective of this research is to create a volleyball smash drill training tool based on voice reaction in the form of an Android application as an innovation and to determine the level of impact produced by the tool. This volleyball smash training tool is equipped with a voice-reacting Android component that can be adjusted according to the user’s needs. Methods: The research employs both qualitative and quantitative research methods using the Research and Development (R&D) approach, encompassing stages such as needs analysis, development planning, expert validation, small-group testing, large-group testing, revisions, and final product development. To assess the effectiveness of the tool, experiments are conducted using the tool during training sessions. Data collection is carried out through observations, interviews, and questionnaires. Both quantitative and qualitative analyses are utilised for data analysis. Findings and Results: The research findings indicate that the Android-based voice command-reactive Acuspike volleyball product is deemed appropriate and can significantly contribute to athlete development, improving game quality, and overall volleyball sports development. However, the limitation of the research lies in the subject being studied at one location. Therefore, further research is recommended for broader generalisation over the long term. Conclusion: In conclusion, volleyball smash skills can be enhanced using the Acuspike volleyball smash tool, emphasising the importance of considering the use of Acuspike tools in both practicing and learning volleyball smash techniques.